Textile-Based Adsorption Sensor via Mixed Solvent Dyeing with Aggregation-Induced Emission Dyes - Hong, Seong Gyun; Oh, Byeong M.; Kim, Jong H.; Lee, Jea Uk (Materials, 2024)
This study demonstrates a novel methodology for developing a textile-based adsorption sensor via mixed solvent dyeing with aggregation-induced emission (AIE) dyes on recycled fabrics. AIE dyes were incorporated into the fabrics using a mixed solvent dyeing method with a co-solvent mixture of H2O and organic solvents. This method imparted unique fluorescence properties to fabrics, altering fluorescence intensity or wavelength based on whether the AIE dye molecules were in an isolated or aggregated state on the fabrics. The precise control of the H2O fraction to organic solvent during dyeing was crucial for influencing fluorescence intensity and sensing characteristics. These dyed fabrics exhibited reactive thermochromic and vaporchromic properties, with changes in fluorescence intensity corresponding to variations in temperature and exposure to volatile organic solvents (VOCs). Their superior characteristics, including a repetitive fluorescence switching property and resistance to photo-bleaching, enhance their practicality across various applications. Consequently, the smart fabrics dyed with AIE dye not only find applications in clothing and fashion design but demonstrate versatility in various fields, extending to sensing temperature, humidity, and hazardous chemicals.
Keywords: Aggregation-induced emission dye; Aggregation-induced emissions; Cosolvent mixtures; Dyeing methods; Fluorescence intensities; Fluorescence properties; Mixed solvent; Novel methodology; Recycled fabric; Solvent dyeing; aggregation-induced emission dyes; recycled fabric; sensor; smart textile; solvent dyeing